2017
DOI: 10.1088/1361-6528/aa655f
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the transformation of aliphatic and fullerene molecules by high-energy electrons using surface-enhanced Raman spectroscopy

Abstract: We report on using 100 keV electrons to obtain amorphous carbon from aliphatic and fullerene molecules, and study this process by monitoring their Raman signal. In this regard, we use self-assembled monolayers of gold nanoparticles to provide high electromagnetic field enhancement, which allows the detection of the Raman signal from even nanometer-thick layers of analyte. Our results show different dynamics in the amorphization process of the two molecules, although both show suppression of their original vibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…38 Structural transformation of both aliphatic SAMs and fullerene molecules into amorphous carbon by high-energy electrons has been recently investigated using SERS. 39 In this paper, we use biphenylthiol (BPT), 4′-nitro-1,1′biphenyl-4-thiol (NBPT), and p-terphenylthiol (TPT) as model molecules to form SAMs on Au(111) and prepare CNMs via electron irradiation. SERS assisted by Au NPs is employed not only to confirm the chemisorption of precursor molecules on Au surfaces but also to monitor structural changes involved in the conversion of pristine SAMs to cross-linked monolayers induced by electron-beam irradiation.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Structural transformation of both aliphatic SAMs and fullerene molecules into amorphous carbon by high-energy electrons has been recently investigated using SERS. 39 In this paper, we use biphenylthiol (BPT), 4′-nitro-1,1′biphenyl-4-thiol (NBPT), and p-terphenylthiol (TPT) as model molecules to form SAMs on Au(111) and prepare CNMs via electron irradiation. SERS assisted by Au NPs is employed not only to confirm the chemisorption of precursor molecules on Au surfaces but also to monitor structural changes involved in the conversion of pristine SAMs to cross-linked monolayers induced by electron-beam irradiation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…SERS has been used to characterize the bonding, structure, and orientation of adsorbed molecules at Au and Ag surfaces. On the other hand, SAMs have been employed as model systems to study the influence of nanoparticle (NP) shapes and their optical properties on the SERS enhancement factors . Structural transformation of both aliphatic SAMs and fullerene molecules into amorphous carbon by high-energy electrons has been recently investigated using SERS …”
Section: Introductionmentioning
confidence: 99%
“…Fullerenes, such as C 60 , have attracted enormous interest both theoretically and experimentally due to their unique physiochemical properties. Concretely, C 60 can be reversibly reduced by accepting up to six electrons and exhibited wide absorption in the whole UV–vis range, making it an attractive photoactive probe in constructing PEC biosensors. However, few studies have been reported for the applications of fullerenes in the research areas of PEC biosensing, partially due to the low electronic conductivity and poor interfacial interactions with biomolecules. In principle, prospective properties could be achieved by a rational modification of fullerene into potential derivatives. In our previous work, we showed that the solubility of fullerene in organic solvents could be immensely enhanced by modifying fullerene with three long alkyl chains via a Prato reaction, and the photoelectric conversion efficiency of alkylated fullerene C 60 (AC 60 ) could be greatly improved by assembling with graphene due to the high affinity of long alkyl chains to the graphene …”
mentioning
confidence: 99%